2001
DOI: 10.1007/s004380000357
|View full text |Cite
|
Sign up to set email alerts
|

The complete DNA sequence of the mitochondrial genome of Physarum polycephalum

Abstract: The complete sequence of the mitochondrial DNA (mtDNA) of the true slime mold Physarun polycephalum has been determined. The mtDNA is a circular 62,862-bp molecule with an A+T content of 74.1%. A search with the program BLAST X identified the protein-coding regions. The mitochondrial genome of P. polycephalum was predicted to contain genes coding for 12 known proteins [for three cytochrome c oxidase subunits, apocytochrome b, two F1Fo-ATPase subunits, five NADH dehydrogenase (nad) subunits, and one ribosomal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 24 publications
(46 reference statements)
6
57
0
Order By: Relevance
“…Therefore, the first 43 amino acids were assumed to be a mitochondrial transit peptide resulting in a mature protein of 283 amino acids. This is consistent with Pmn34 being encoded by the nuclear genome, as the mitochondrial genome does not contain the Pmn34 gene (Takano et al 2001). A BLAST search against the Pfam database revealed that Pmn34 was predicted to encode a putative DEDD (DnaQlike) exonuclease superfamily protein that catalyzes the excision of nucleoside monophosphates at DNA or RNA termini in the 3Ј to 5Ј direction (Pfam, cd06127, E-value 7e-11) (Fig.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Therefore, the first 43 amino acids were assumed to be a mitochondrial transit peptide resulting in a mature protein of 283 amino acids. This is consistent with Pmn34 being encoded by the nuclear genome, as the mitochondrial genome does not contain the Pmn34 gene (Takano et al 2001). A BLAST search against the Pfam database revealed that Pmn34 was predicted to encode a putative DEDD (DnaQlike) exonuclease superfamily protein that catalyzes the excision of nucleoside monophosphates at DNA or RNA termini in the 3Ј to 5Ј direction (Pfam, cd06127, E-value 7e-11) (Fig.…”
Section: Resultssupporting
confidence: 66%
“…By contrast, the true slime mold Physarum polycephalum has an extraordinarily large amount of mtDNA in its rod-shaped mtnucleoids, with a long axis of ϳ1.5 mm (Kuroiwa 1974, making it a good model organism to study the function of mt-nucleoid. The mtDNA of P. polycephalum is composed of a circular molecule of 62,862 bp (Takano et al 2001), and at least 40 and 80 copies of mtDNA molecules are contained in each mt-nucleoid at the mitochondrial G1 and G2 phases, respectively (Kuroiwa and Kuroiwa 1980). A method for obtaining highly purified mt-nucleoids from P. polycephalum, without the contamination of cell nuclei, has been established (Sasaki et al 1998).…”
mentioning
confidence: 99%
“…Six different types of dinucleotide insertions have been reported in Physarum mitochondrial RNAs: CU, GU, GC, UA, UU, and AA (7,(10)(11)(12)(13)16). As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…These data argue that at least a portion of the nascent RNA synthesized in vivo has CA rather than UA inserted at es31/32. There are six known cases in which two identical nucleotides are added at adjacent sites: two sites of AA insertion in both the small-subunit (SSU) rRNAs (10) and large-subunit rRNAs (11) and 2 UU nucleotides in the nd7 mRNA (12). Each of these insertions occurs in an ambiguous context (Fig.…”
Section: Vol 24 2004 Dinucleotide Insertions In Physarum 7823mentioning
confidence: 99%
See 1 more Smart Citation